PENOLAKAN PEMERINTAH INDONESIA TERHADAP PERUBAHAN TARIF PAJAK CPO (CRUDE PALM OIL) OLEH PERANCIS 2016 - Desi Amelia; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research aims to explain economy and politic interests from the Rejection of Indonesian Government for changing Crude Palm Oil (CPO) taxes tariff by France. CPO is one of the most agriculture commodities that Indonesia had in this century. Since 2010, CPO trade have faced with black campaign by Greenpeace and impacted to regulation of vegetable oil products in European Union market and France included in it. The differences of regulation between CPO and others vegetable oil are Renewable Energy Directive, Labelling regulation and taxes tariff. The changing of CPO Taxes Tariff that is planning will begin to use in 2017 and the reason is sustainability principle got attention from CPO Producer countries include Indonesian.Data of this research was obtained from books, journals, articles, official documents and websites that support the hypothesis. The author used nation-state level analyze, the theories used in this research consist of Foreign Policy Foreign Policy theory by James N. Rosenau, the national interest by Hans J. Morgenthau.The result of this research shows that there is an economy politic interest in the rejection of Indonesian Government for changing Crude Palm Oil (CPO) taxes tariff by France that will impact negatively for export value on CPO if the policy like this success used. The regulation for opening of palm oil plantations that was often become problem now have been maximize for interests both of CPO producer and exporter. CPO also become one of the keys on economic growth and village development in Indonesia. In addition, the CPO price and tax ratio in France was not indicate that CPO tax rates need to be raised.Keyword: taxes tariff, CPO, national interests, economy politic, regulates